Development of technique of Backward integration step-by-step for solve stiff initial value problems - Khalid A. M. Khalaf; Bashir M. S. Khalaf (Tikrit Journal of Pure Science, 2023)
Our purpose in this paper is the development of the  technique of backward integration step-by-step, In order to facilitating the use of this technique for  solving  the Stiff Problems. When using backward integration step-by-step for solving one differential equation of first order we need to solve () algebraic equations while using the new developed technique we need solve one algebraic equation. In general if the order of the differential equation is (), the solution needs solving ()of algebraic equation by using backward integration step-by-step. While the  developed technique needs only solving () of algebraic equations.